Hungerkrisen - Genese und Bewältigung von Hunger in ausgewählten Territorien Nordwestdeutschlands 1690-1750 - Lassen, Thore (Universitätsverlag Göttingen, 2016)
For the people in the Early Modern Age, famines were regularly recurring phenomena. So not less than eight of these crises happened in the areas of Lower Saxony between 1690 and 1750, which had a lasting impact on various aspects of life for the contemporaries. Therefore topics of different historical subdisciplines like economic, social, cultural and environmental history are dealt with in this dissertation. Thus, this thesis aims to bridge the gap between climatically and socially determined patterns of hunger. With the help of the concept of vulnerability it is shown that hunger crises can neither be ascribed to natural processes nor human operations exclusively. In fact they were the outcome of a chain of human-nature-interactions and were perceived as such by the contemporaries. A further emphasis of this book is put on the examination of contemporary coping strategies. The hereby worked out explanatory and interpretive models proved to be determining how the contemporaries tried to cope with hunger on a personal and joint level. Regarding the latter it is shown that famines played a decisive role in the consolidation of leadership in the Early Modern Age. Because of their regular recurrence they worked as focal points of the negotiation of sovereignity between authorities and subjects more than any other crisis situation in this process.